Deciphering the evolutionary signatures of pinnipeds using novel genome sequences: The first genomes of Phoca largha, Callorhinus ursinus, and Eumetopias jubatus. Issue 1 (December 2018) - Park, Jung; Kim, Kwondo; Sohn, Hawsun; Kim, Hyun; An, Yong-Rock; Kang, Jung-Ha; Kim, Eun-Mi; Kwak, Woori; Lee, Chul; Yoo, DongAhn; Jung, Jaehoon; Sung, Samsun; et al.
Abstract The pinnipeds, which comprise seals, sea lions, and walruses, are a remarkable group of marine animals with unique adaptations to semi-aquatic life. However, their genomes are poorly characterized. In this study, we sequenced and characterized the genomes of three pinnipeds (Phoca largha, Callorhinus ursinus, andEumetopias jubatus ), focusing on site-wise sequence changes. We detected rapidly evolving genes in pinniped lineages and substitutions unique to pinnipeds associated with amphibious sound perception. Phenotypic convergence-related sequence convergences are not common in marine mammals. For example, FASN, KCNA5, andIL17RA contain substitutions specific to pinnipeds, yet are potential candidates of phenotypic convergence (blubber, response to hypoxia, and immunity to pathogens) in all marine mammals. The outcomes of this study will provide insight into targets for future studies of convergent evolution or gene function.